2011
DOI: 10.1063/1.3581056
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer energy for Y2O3:Eu3+ nanophosphor

Abstract: Based on the Kronig–Penney model, the changing tendency of the bandgap or of a particular level with the volume deformation in crystalline materials has been derived. On the basis of this changing tendency, the zero-phonon charge transfer (CT) energy is deduced to be decreased when the size of Y2O3:Eu3+ phosphor decreases into the nanoscale. In addition, the rigidity decrease of the lattice environment in Y2O3:Eu3+ nanophosphor leads to the enlargement of the CT state coordinate offset of the optical centers; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…We presented the detailed discussion about parameters influencing the exact CT position in our previous work (Banski et al 2010). Moreover, the observed position of absorption band is in a good agreement with the literature values equal to 240–255 nm for Y 2 O 3 :Eu 3+ (Shang et al 2011).
Fig.
…”
Section: Optical Propertiessupporting
confidence: 91%
“…We presented the detailed discussion about parameters influencing the exact CT position in our previous work (Banski et al 2010). Moreover, the observed position of absorption band is in a good agreement with the literature values equal to 240–255 nm for Y 2 O 3 :Eu 3+ (Shang et al 2011).
Fig.
…”
Section: Optical Propertiessupporting
confidence: 91%
“…However, the increasing effect of the polarizability of the cation by inserting more and more Eu 3+ in the lattice might well lead to a deviation from linearity as shown by the E CT -curve. The JR-2 line in Fig 9 suggests 9 According to these authors the change of the bandgap energy E g can be written as:…”
Section: Figsmentioning
confidence: 99%
“…Jia et al 8 measured a redshift of the E CT of 6 nm upon particle size reduction from 2-3 μm to 7 nm. Shang et al 9 and Zhang et al 10 reported large red shifts, 11 nm and 7 nm, in reducing the size of Y 2 O 3 :Eu 3+ nanoparticles from 40 nm to 9 nm and from 40 nm to 5 nm respectively. Semiconductor particles are expected to show a blueshift of their absorption peaks in reducing the particle size from 15 to 5 nm because of quantum confinement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several oxide host materials are available for the preparation of rare earth doped luminescent materials, but the Y 2 O 3 is chosen due to their high optical band gap, low phonon frequency and ionic radii comparable with most of the rare earths. Several studies have been reported on synthesis and optical characterisation of nanocrystalline Eu 3+ doped phosphors [7,8]. But, the upconversion (UC) emission with NIR excitation in singly Eu 3+ doped materials is not possible.…”
Section: Introductionmentioning
confidence: 99%